PENGARUH KUALITAS DAN HARGA PRODUK BENIH JAGUNG HIBRIDA BISI-18 TERHADAP KEPUASAN PETANI DI KALURAHAN BANYUSOCO, KAPANEWON PLAYEN, KABUPATEN GUNUNGKIDUL - Ribut Siti Nuranisyah; Nanang Kusuma Mawardi; Eska Stefani (JURNAL ILMIAH AGRITAS, 2024)
The aim of this research is to determine the effect of the quality and price of BISI-18 hybrid corn seed products on farmer satisfaction in Banyusoco Village, Playen District, Gunungkidul Regency. This research is a quantitative research with sample determination using the Slovin formula, obtaining 85 respondents from a population of 489 taken from each farmer group in Banyusoco village. The data analysis method used is the quantitative descriptive method by calculating the score value for each variable and the multiple linear analysis method. The research results show that the quality variable score is 3,976, which is in the high category, the price variable score is 2,059, which is in the medium category, and the satisfaction variable score is 3,016, which is in the high category. The results of the t test show that the significant value of X1 is 0.000 < 0.05 and This is because farmers look more at quality than price. The calculated F test shows a value of 8,623 > 3.11 (Ftable), with a significant value of 0.000 < 0.05, so the hypothesis is accepted or in other words the quality and price variables, together simultaneously influence farmer satisfaction. Based on the determination test, the Adjusted R Square value or coefficient of determination is 0.154, which means that the influence of the independent variables, namely quality and price, on the dependent variable, namely satisfaction, is 15.4%, while the remaining 84.6% is influenced or explained by other variables not included in the model this research, such as place factors, service quality, experience, strategy, etc. Keywords: BISI-18 Hybrid Corn Seeds, Quality, Price, Farmer Satisfaction